Effect of fuel content on luminescence and antibacterial properties of zinc oxide nanocrystalline powders synthesized by the combustion method. Issue 100 (13th October 2016) - Pathak, Trilok K.; Kumar, Ashwini; Swart, C. W.; Swart, H. C.; Kroon, R. E.
Abstract : Nanoscale ZnO powders were synthesized via the combustion method using zinc nitrate hexahydrate as the source (oxidant) material and urea, and glycine or citric acid monohydrate as fuels. Abstract : Nanoscale ZnO powders were synthesized via the combustion method using zinc nitrate hexahydrate as the source (oxidant) material and urea, and glycine or citric acid monohydrate as fuels. The effect of the relative fuel to oxidant ratio on the characteristics of ZnO particles produced with urea as the fuel was also investigated. X-ray diffraction analysis revealed that the ZnO nanocrystalline particles were successfully synthesized by combustion and the crystallite size was different depending on the fuel. The surface morphology showed a dramatic change as the fuel changed in the synthesis process. The chemical states of the synthesized ZnO powders were investigated using X-ray photoelectron spectroscopy, which allowed an assessment of the Zn and O related defect concentrations. The optical bandgap varied from 3.12 to 3.14 eV for different fuels and it decreased to 3.10 eV in the fuel rich case for urea. The maximum defect level photoluminescence emission was observed for the ZnO powder synthesized using urea as the fuel, for the stoichiometric fuel mix. All products exhibited similar antibacterial effects; however they had a greater effect on Staphylococcus aureus compared to Escherichia coli .